2002
DOI: 10.1128/aac.46.3.731-738.2002
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Resistance to Protease Inhibitor Amprenavir in Human Immunodeficiency Virus Type 1-Infected Patients: Selection of Four Alternative Viral Protease Genotypes and Influence of Viral Susceptibility to Coadministered Reverse Transcriptase Nucleoside Inhibitors

Abstract: Previous data have indicated that the development of resistance to amprenavir, an inhibitor of the human immunodeficiency virus type 1 protease, is associated with the substitution of valine for isoleucine at residue 50 (I50V) in the viral protease. We present further findings from retrospective genotypic and phenotypic analyses of plasma samples from protease inhibitor-naïve and nucleoside reverse transcriptase inhibitor (NRTI)-experienced patients who experienced virological failure while participating in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 34 publications
(30 reference statements)
5
69
1
Order By: Relevance
“…D30N, G48V, I54V, V82A/T/S/F and L90M) are not selected by APV in vivo or in vitro [1]. Data from clinical studies [3][4][5] have confirmed that the incidence of cross-resistance to APV following treatment with other PIs is markedly lower than that observed with other PIs.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…D30N, G48V, I54V, V82A/T/S/F and L90M) are not selected by APV in vivo or in vitro [1]. Data from clinical studies [3][4][5] have confirmed that the incidence of cross-resistance to APV following treatment with other PIs is markedly lower than that observed with other PIs.…”
Section: Introductionsupporting
confidence: 52%
“…Mutations key for resistance to other PIs (e.g. D30N, G48V, V82A/T/S/F or L90M) are not selected with APV in vivo or in vitro [1], and the incidence of cross-resistance to APV in PI-experienced subjects is markedly lower than that observed with other PIs [3,4]. The distinct resistance profile of APV may help to make available another treatment option for PI-experienced patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that PR insertions, particularly those between residues 32 and 42, have become more prevalent since 1999. These insertions are positively correlated with PR codons associated with resistance to PIs whose usage has increased in recent years, including atazanavir (position 16) (38), lopinavir and amprenavir (position 47) (21,17), and tipranavir (positions 13, 36, and 47) (11). Additionally, a mutation at position 57 is a predictor of early virologic failure (23), and codon 91 mutations are more common in patients on long-term nonsupressive PI therapy (16).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published sequence data on protease inhibitorassociated mutations are based on isolates obtained from persons treated for no more than 1 year with a single inhibitor (4,17,(19)(20)(21). Few published data are available from persons with carefully characterized treatment histories who have received more than one inhibitor (12), and the genetic mechanisms by which HIV-1 protease develops resistance to multiple inhibitors have not been explored.…”
mentioning
confidence: 99%